A 1 cm2 Organic Solar Cell with 15.2% Certified Efficiency: Detailed Characterization and Identification of Optimization Potential. Issue 4 (15th February 2021) - Würfel, Uli; Herterich, Jan; List, Mathias; Faisst, Jared; Bhuyian, Md Fahmid Matin; Schleiermacher, Hans-Frieder; Knupfer, Klara T.; Zimmermann, Birger
Abstract : In organic photovoltaics, high power conversion efficiencies (PCE) are mostly achieved on device areas well below 0.1 cm 2 . Herein, organic solar cells based on a D18:Y6 absorber layer on an active area of ≥ 1 cm 2 with a certified PCE of 15.24% are reported. The impacts of the sheet resistance of the transparent electrode and the cell design are quantified by means of full optical device simulations and an analytical electrical model. Three imaging methods (light beam‐induced current, dark lock‐in thermography, and electroluminescence [EL]) are applied and reveal a strong homogeneity of the record cell. Nevertheless, it is found that there is substantial room for improvement mostly in current but also in fill factor and that a PCE of 18.6% on ≥1 cm 2 is feasible with this absorber material. Further, photoluminescence (PL) and EL spectroscopy reveal that both emissions occur at the same wavelength(s) and are very similar to the PL spectrum of a pure Y6 acceptor film. The latter points strongly toward electronic coupling between the S1 states of the acceptor and the charge transfer states at the donor/acceptor interface. Abstract : A record efficiency of 15.24% is achieved for organic solar cells with an area of ≥1 cm 2 with D18:Y6 as absorber material. The optimized cell design minimizes resistive losses due to the indium tin oxide (ITO) electrode. The cell is very homogeneous and is hardly affected by shunts, as revealed by light beam‐induced current, electroluminescence, and dark lock‐in thermography imaging.